Selective Regulation of Apoptosis: the Cytotoxic Lymphocyte Serpin Proteinase Inhibitor 9 Protects against Granzyme B-Mediated Apoptosis without Perturbing the Fas Cell Death Pathway - Bird, Catherina H. (American Society for Microbiology, 1998)
Cytotoxic lymphocytes (CLs) induce caspase activation and apoptosis of target cells either through Fas activation or through release of granule cytotoxins, particularly granzyme B. CLs themselves resist granule-mediated apoptosis but are eventually cleared via Fas-mediated apoptosis. Here we show that the CL cytoplasmic serpin proteinase inhibitor 9 (PI-9) can protect transfected cells against apoptosis induced by either purified granzyme B and perforin or intact CLs. A PI-9 P(1) mutant (Glu to Asp) is a 100-fold-less-efficient granzyme B inhibitor that no longer protects against granzyme B-mediated apoptosis. PI-9 is highly specific for granzyme B because it does not inhibit eight of the nine caspases tested or protect transfected cells against Fas-mediated apoptosis. In contrast, the P(1)(Asp) mutant is an effective caspase inhibitor that protects against Fas-mediated apoptosis. We propose that PI-9 shields CLs specifically against misdirected granzyme B to prevent autolysis or fratricide, but it does not interfere with homeostatic deletion via Fas-mediated apoptosis.